2015
DOI: 10.1002/cyto.b.21317
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry screening for paroxysmal nocturnal hemoglobinuria: A single‐center experience in Saudi Arabia

Abstract: Results: Of the 366 samples submitted for PNH screening, 14 were positive (4%) and 11 were evaluable. Of the 11 patients analyzed, 8 patients (73%) presented with aplastic anemia, 1 patient (9%) each with pancytopenia, Budd-Chiari syndrome, and immune thrombocytopenia purpura. All samples showed type II and III GPI-deficient clones with a median clone size of 15% (range, 0.7%-56%) in the RBCs, and 63% (range, 3.8%-100%) in WBCs (monocytes and granulocytes).Conclusions: This study confirms the rarity of PNH and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A study on the Saudi population showed 4% detectable PNH clones in tested patients, albeit 73% of them presented with AA. 19 In our cohort, more than half of the diagnosed patients had classical PNH with manifestations of DAT-negative hemolytic anemia and large PNH clones (> 60% neutrophils and monocytes). One of these patients presented with hemolytic anemia, aplastic marrow, and a large PNH clone, suggesting an overlap presentation.…”
Section: Discussionmentioning
confidence: 71%
“…A study on the Saudi population showed 4% detectable PNH clones in tested patients, albeit 73% of them presented with AA. 19 In our cohort, more than half of the diagnosed patients had classical PNH with manifestations of DAT-negative hemolytic anemia and large PNH clones (> 60% neutrophils and monocytes). One of these patients presented with hemolytic anemia, aplastic marrow, and a large PNH clone, suggesting an overlap presentation.…”
Section: Discussionmentioning
confidence: 71%
“…In agreement with former studies, results of the current report show that the PNH clone sizes on RBCs are significantly smaller than clones on WBCs with a p ‐value <0.0001 using a Mann–Whitney test. This difference may be due to previous blood transfusions or the increased rate of haemolysis within this cohort of patients [ 19 ]. There's also a significant correlation between PNH clone sizes on different cell lineages with a Spearman r of 0.7316 for PNH clones on granulocytes and monocytes, and a Spearman r of 0.7813 for PNH clones on RBCs and granulocytes.…”
Section: Discussionmentioning
confidence: 99%